Antioxidant and Cytotoxic Potential of Local Endemic Plant Pastinaca zozimoides Fenzl - Cihan Düşgün; Teoman Kankılıç; Cemil İşlek; Dilara Fatma Balı; Özgür Kankılıç (Turkish Journal of Agriculture: Food Science and Technology)
P. zozimoides is local endemic in Nigde province, Turkey. There has been no previous examination of the chemical composition and bioactivity of that plant extract. In this study, we studied total phenolic content, antioxidant properties and cytotoxic effect of methanolic extracts of plant sample. According to the Folin-Ciocalteau method, the total phenolics of the extracts were determined spectrophometric. The antioxidant activity was conducted DPPH (1,1’-diphenyl-2-picrylhydrazyl) radical scavenging method and free radical reducing power assay. The cytotoxic effect was studied using MTT assay cell viability on cancer cell lines as well as on Caco-2 cell lines. The total phenolic content of P. zozimoides extract was found 28.79±0.68 μg GAE /mg. The free radical scavenger activities of the DPPH was 31.69%±1.61, 85.15%±0.13, 86.96%±0.085 for 1, 5 and 10 mg/mL, respectively. The free radical reducing power assay was 0.375±0.52, 1.587±0.71, 1.798±0.84 for 1, 5 and 10 mg/mL compared to ascorbic acid standard. On Caco-2 cell lines, the extract of plant showed no cytotoxic potential. Because of its phenolic constituents and its antioxidant capacity it can be considered a healthy nutrient.